2021
DOI: 10.1590/s1677-5538.ibju.2021.0253
|View full text |Cite
|
Sign up to set email alerts
|

Does previous standard percutaneous nephrolithotomy impair retrograde intrarenal surgery outcomes?

Abstract: Purpose: The objective of this study is to evaluate the impact of a previous standard percutaneous nephrolithotomy (PCNL) on the outcomes of retrograde intrarenal surgery (RIRS). Materials and Methods: Outcomes of RIRS performed from January 2017 to January 2020 in adult patients with residual stone fragments ≤20mm after a standard PCNL (Post-PCNL) and symptomatic adult patients with kidney stones ≤20mm (Control) were prospectively studied. Stone-free rate (SFR) was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In contrast, studies focusing exclusively on the preoperative scenario have indicated that seven days of oral antibiotics before PCNL can reduce the incidence of SIRS/sepsis, as well as the positivity of intraoperative urine culture and stone culture (26). It's important to note that many, but not all, of the patients included in these studies had some infectious risk factors, such as larger stone size, positive preoperative urine culture, dilated pelvicalyceal system, or the presence of an indwelling ureteral stent or nephrostomy tube (26).…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, studies focusing exclusively on the preoperative scenario have indicated that seven days of oral antibiotics before PCNL can reduce the incidence of SIRS/sepsis, as well as the positivity of intraoperative urine culture and stone culture (26). It's important to note that many, but not all, of the patients included in these studies had some infectious risk factors, such as larger stone size, positive preoperative urine culture, dilated pelvicalyceal system, or the presence of an indwelling ureteral stent or nephrostomy tube (26).…”
Section: Discussionmentioning
confidence: 98%
“…Zhou et al concluded that ultrasound-guided balloon dilation simplifies the access creation process, reduces the potential trauma associated with continuous operation of the Amplatz dilator, and results in fewer bleeding complications ( 15 ). Danilovic et al reveals infundibula strictures can be found in 26.3% of the patients with residual stone fragments after standard PCNL for large burden kidney stones ( 31 ). This meta-analysis revealed a slightly lower complication rate in the balloon group (12.56%) compared to the non-balloon group (13.86%), although the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 30 years, the incidence of upper urinary tract calculi has been increasing continuously ( 16 ). The harm of upper urinary tract calculi to the human body is significant ( 17 , 18 ). Although PCNL is one of the primary methods for the treatment of upper urinary tract calculi, PCNL cannot completely eliminate stone fragment residues.…”
Section: Discussionmentioning
confidence: 99%